Examining the Economic Impact of the Massage & SPA Business in Batam through Social Media Analysis - Cristina, Cristina; Andelson, Jeffrey; Lim, Jesson (Jurnal Ekonomi Balance, 2024)
This study investigates the economic impact of the Massage & SPA business in Batam by leveraging social media analysis. The research aims to assist small and medium enterprises (SMEs) in enhancing their branding strategies through platforms like Instagram. Using qualitative methods including interviews, observations, and documentation, the study identifies key areas where researchers can aid in business growth. The findings reveal that the strategic use of social media significantly boosts the visibility and customer engagement of Massage & SPA businesses. Timely financial support and flexible repayment options have effectively reduced default rates and promoted business scalability. However, limitations exist due to the lack of pre-financing condition data of SMEs, requiring cautious interpretation of results. The study underscores the continuous growth of outstanding performance annually and the positive outcomes for fund recipients. Recommendations for the businesses include increasing social media activity and expanding to additional platforms to reach a broader audience.